NASIONALISME H.O.S. TJOKROAMINOTO DALAM FILM GURU BANGSA HOS TJOKROAMINOTO KARYA SUTRADARA GARIN NUGROHO - Dewi Puspitasari; Retno Dewi Ambarastuti (Puitika)
HOS Tjokroaminoto is one of national heroes known as Guru Bangsa (Teacher of the Nation). Tjokroaminoto gets this title as he and his thought inspire Indonesian political figures. Tjokroaminoto is the only person in the beginning of 20th century who vocally and bluntly stated that Indies (Indonesia) had to establish its own governance. It is then termed the independence. Independence can be realized with the awareness of national consciousness in the national level, not in local level anymore.